STUDI PEMBANGKITAN TORSI PADA CAKRAM BAJA MENGGUNAKAN GAYA-MEDAN MAGNET NEODYMIUM - Sigit Iswahyudi; Wandi Arnandi (Wahana Ilmuwan, 2017)
This works is a preliminary study that evaluates probability of torque generation in steel disc by field force of neodymium magnet. The study was started by analyzing ferromagnetic disc that is surrounded by magnets. In simulation, the disc had a diameter of 400 m and was made of S416. The magnets used in the simulation had cubed form and length of 10 mm. The magnets were placed around the disc in such a way that the center of their poles made an angle of 42 degrees from the disc radii. The nearest distance between center magnet poles to the center of the disc was 210.6 mm. There were six configurations of magnets to be evaluated, i.e. configurations of 1, 2, 4, 8, 16 and 32 magnets. Effects of magnet configurations on torque generation in the disc were evaluated by using MagNet software. Simulation results show that the highest torque was achieved by 16 magnet configuration.